2014
DOI: 10.1016/j.bgm.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin decreased level of proinflammatory cytokines in monocyte cultures exposed to preeclamptic plasma by affecting the transcription factors NF-κB and PPAR-γ

Abstract: The purpose of this study is to determine the role of curcumin in the alteration of levels of interleukin (IL)-1a, IL-6, and tumor necrosis factor a (TNF-a) as proinflammatory cytokines in monocyte culture exposed to preeclamptic plasma, as well as the effect on the transcription factors: nuclear factor kappa beta (NF-kB) and peroxisome proliferator-activated receptor g (PPAR-g). Plasma was taken from preeclamptic women (n Z 12) and normotensive pregnant women (n Z 12). Monocyte cultures were taken from nonpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…Moreover, by blocking the ROS cascade, curcumin can inhibit downstream reactions of nuclear factor kappa-B (NF-κB) and prevent the deleterious effects of TNF mediators. Other anti-inflammatory effects of nanocurcuminoids can be instigated by shifting Th1 towards Th2 and its derivate, preparing an anti-inflammatory state (Edwards et al, 2017[ 10 ]; Rahardjo et al, 2014[ 36 ]; Toden et al, 2017[ 46 ]; Yu et al, 2018[ 49 ]). Most of these studies have proven that curcumin at higher concentrations (>20 µM) exhibit superior functionality in lowering inflammatory cytokines (Edwards et al, 2017[ 10 ]; Rahardjo et al, 2014[ 36 ]; Yu et al, 2018[ 49 ]), while we found the opposite outcome - that low doses of nanocurcuminoids are more beneficial in reducing inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by blocking the ROS cascade, curcumin can inhibit downstream reactions of nuclear factor kappa-B (NF-κB) and prevent the deleterious effects of TNF mediators. Other anti-inflammatory effects of nanocurcuminoids can be instigated by shifting Th1 towards Th2 and its derivate, preparing an anti-inflammatory state (Edwards et al, 2017[ 10 ]; Rahardjo et al, 2014[ 36 ]; Toden et al, 2017[ 46 ]; Yu et al, 2018[ 49 ]). Most of these studies have proven that curcumin at higher concentrations (>20 µM) exhibit superior functionality in lowering inflammatory cytokines (Edwards et al, 2017[ 10 ]; Rahardjo et al, 2014[ 36 ]; Yu et al, 2018[ 49 ]), while we found the opposite outcome - that low doses of nanocurcuminoids are more beneficial in reducing inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of this reproductive disorder is attributed towards increase in the levels of pro‐inflammatory cytokines like TNF‐α, IL‐6, and IL‐1β. Anti‐inflammatory drug like curcumin can be used to treat the inflammatory related diseases via reducing the levels of pro‐inflammatory cytokines . Curcumin reduces inflammation by mitigating genetic, molecular, and epigenetic factors .…”
Section: Discussionmentioning
confidence: 99%
“…After curcumin treatment, there was decreased level of nuclear NF-kB p50 and increased level of PPAR-significantly. 24 In other study, LPS-curcumin-treated group had decreased blood pressure and urinary protein level, which was comparable to control group, as well as improved trophoblast invasion and spiral artery remodeling induced by LPS. Increased TLR4, NF-kB and IL-6, MCP-1 protein expressions in LPS-treated group were significantly decreased after curcumin administration.…”
Section: Discussionmentioning
confidence: 73%